Question 1 of 5Find the inverse:
Select the Correct Answer Below: Correct! Not Correct!
A
$$f^{-1}(x)=\frac{1}{x - 2}+ 1$$
B
$$f^{-1}(x)=\frac{1}{-x - 2}$$
C
$$f^{-1}(x)=\frac{2}{x - 3}+ 4$$
D
$$f^{-1}(x)=\frac{4}{2x - 1}$$
E
$$f^{-1}(x)=\frac{2}{x - 1}- 1$$
Question 2 of 5Find the inverse:
Select the Correct Answer Below: Correct! Not Correct!
A
$$f^{-1}(x)=2x + 3$$
B
$$f^{-1}(x)=\frac{2}{x - 2}+ 3$$
C
$$f^{-1}(x)=\frac{-2}{-x - 2}- 1$$
D
$$f^{-1}(x)=\frac{x + 4}{x + 2}$$
E
$$f^{-1}(x)=\frac{x + 5}{x + 3}$$
Question 3 of 5Find the inverse:
Select the Correct Answer Below: Correct! Not Correct!
A
$$f^{-1}(x)=2(x - 5)^2$$
B
$$f^{-1}(x)=3x^2 - 1$$
C
$$f^{-1}(x)=(x + 2)^3 - 3$$
D
$$f^{-1}(x)=x^3 - 1$$
E
$$f^{-1}(x)=\sqrt[3]{x}+ x - 1$$
Question 4 of 5Find the inverse:
Select the Correct Answer Below: Correct! Not Correct!
A
$$f^{-1}(x)=-2(x - 3)^5$$
B
$$f^{-1}(x)=\sqrt[5]{x - 1}- 2$$
C
$$f^{-1}(x)=\frac{-6 - \sqrt[5]{16x}}{2}$$
D
$$f^{-1}(x)=\sqrt[5]{x + 1}- 2x^5$$
E
$$f^{-1}(x)=3x^5 - 1$$
Question 5 of 5Find the inverse:
Select the Correct Answer Below: Correct! Not Correct!
A
$$f^{-1}(x)=\frac{5x - 3}{x - 2}$$
B
$$f^{-1}(x)=5x + 2$$
C
$$f^{-1}(x)=\frac{3x + 5}{2x + 1}$$
D
$$f^{-1}(x)=\frac{1}{5}x - 3$$
E
$$f^{-1}(x)=\frac{1}{5}x + 3$$

Great Job! You Passed!

Better Luck Next Time...

Restart Quiz ↻
Review Lesson ↻
Next Lesson »